c-erbB-2 expression in different histological types of invasive breast carcinoma. - Soomro, S; Shousha, S; Taylor, P; Shepard, H; Feldmann, M (1991)
Sections of 149 breast carcinomas were examined for the over-expression of c-erbB-2 oncoprotein using the avidin-biotin immunoperoxidase technique and two different specific antibodies. These included the polyclonal antibody 21N and the monoclonal antibody 4D5. The tumours were divided into two main groups. The first included 75 cases of invasive ductal and classic invasive lobular carcinomas. The second group consisted of 74 cases with histological types known to have a good prognosis, including mucinous, alveolar variant of invasive lobular, medullary, tubular, cribriform and papillary carcinomas. Fifteen (20%) tumours of the first group were positive with the two antibodies. Fourteen of these were of the ductal type and one was a mixed invasive ductal and lobular carcinoma. Ten of the pure ductal cases had areas of comedo carcinoma. The intraductal elements in a further tumour were positively stained with 21N antibody only. None of the second group of tumours, which included histological types known to have good prognosis, stained with 4D5, although one mucinous carcinoma was positively stained with 21N. These findings suggest that in invasive breast carcinoma immunostaining for c-erbB-2 is mainly seen in a subgroup of ductal tumours, and that almost all other histological types, especially those associated with good prognosis, lack this expression.